Accessing rehabilitation after stroke – a guessing game?. Issue 7 (27th March 2017) - Enderby, Pam; Pandyan, Anand; Bowen, Audrey; Hearnden, David; Ashburn, Ann; Conroy, Paul; Logan, Pip; Thompson, Carl; Winter, Jacqueline
Abstract: Aim: To explore the use, meaning and value of the term "rehabilitation potential". Method: The authors of this commentary met to discuss concerns relating to the pressure on health service staff created by reduced length of stay in acute settings of those who have suffered a stroke and the need to determine the potential of a patient for rehabilitation in order to inform discharge arrangements. Points raised at this meeting were shared with an email group who over a 12-month period contributed to this paper. Results: The group agreed that: (a) Given that there is very limited evidence to guide judgements regarding rehabilitation potential following stroke at an early stage the need for rehabilitation needs to be reviewed on a regular basis over a long period and that this needs to be reflected in clinical guidelines. (b) Rehabilitation needs to be available in a broad range of care settings, in order that discharge from hospital is not equated with a lack of rehabilitation potential. (c) Research related to rehabilitation potential needs to be conducted. This should examine influences of decision-making and the algorithms associated with recovery and local policy on rehabilitation potential. (d) The economic benefits of rehabilitation needs further exploration. (e) Assessment of rehabilitation potential should be made more explicit and supported by appropriate evidence. Conclusion: Whilst further research is required to assist in determining the right time for people to benefit from formal rehabilitation this gives the impression that one dose of rehabilitation at a specific time will meet all needs. It is likely that a rehabilitation pathway identifying features required in the early stages following stroke as well as that required over many years in order to prevent readmission, maintain fitness and prevent secondary sequelae such as depression and social isolation would be beneficial. Implications for Rehabilitation: The potential of a patient to benefit from rehabilitation may be overlooked due to other pressures. Some patients following a stroke will demonstrate potential to benefit from rehabilitation later than the majority and this is not always easy to predict. Regular reassessment is required in order to identify whether an individual will benefit from rehabilitation at a particular time.